Chemical Composition Data of the Main Stages of Copper Production from Sulfide Minerals in Chile: A Review to Assist Circular Economy Studies - Cifuentes-Molina, G (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
The mining industry has faced significant challenges to maintaining copper production technically, economically, and environmentally viable. Some of the major limitations that must be overcome in the coming years are the copper ore grade decline due to its intense exploitation, the increasing requirements for environmental protection, and the need to expand and construct new tailings dams. Furthermore, the risk of a supply crisis of critical metals, such as antimony and bismuth, has prompted efforts to increase their extraction from secondary resources in copper production. Therefore, improving conventional processes and developing new technologies is crucial to satisfying the world’s metal demands, while respecting the policies of environmental organizations. Hence, it is essential that the chemical composition of each copper production stage is known for conducting these studies, which may be challenging due to the huge variability of concentration data concerning the ore extraction region, the process type, and the operational conditions. This paper presents a review of chemical composition data of the main stages of copper production from sulfide minerals, such as (1) copper minerals, (2) flotation tailings, (3) flotation concentrates, (4) slags and (5) flue dust from the smelting/converting stage, (6) copper anodes, (7) anode slimes, (8) contaminated electrolytes from the electrorefining stage, (9) electrolytes cleaned by ion-exchange resins, and (10) elution solutions from the resins. In addition, the main contributions of recent works on copper production are summarized herein. This study is focused on production sites from Chile since it is responsible for almost one-third of the world’s copper production. © 2022 by the authors. Licensee MDPI, Basel, Switzerland.